Penerapan Integrated Node Capture Attitude Record Terhadap Pelanggaran Lalu Lintas Di Wilayah Polres Trenggalek - Andhiya Moza Faris; Elan Jaelani; Hasan Bisri (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This study is driven by the increasing number of traffic violations in Indonesia highlighting the need for more effective and transparent law enforcement mechanisms. This research aims to examine the implementation of Integrated Node Capture Attitude Record (INCAR) by the Trenggalek Police Department, identify the challenges encountered, and evaluate the strategies adopted in response. A descriptive-analytical method with an empirical juridical approach was employed, utilizing primary data from interviews and secondary data from books and academic journal articles. The findings indicate that INCAR operates under two patrol models: targeted patrols in high-violation areas and random patrols. Offenders are provided with two options: pay fines via a BRIVA payment code or appear in court. Major challenges include a limited number of operational units, low public legal awareness, and the absence of certain expected features. In response, the police have adopted a hybrid enforcement strategy by combining manual ticketing with INCAR, alongside public education initiatives.